2021
DOI: 10.1097/j.jcrs.0000000000000633
|View full text |Cite|
|
Sign up to set email alerts
|

Repeatability of 2 swept-source OCT biometers and 1 optical low-coherence reflectometry biometer

Abstract: To compare the repeatability of 2 swept-source optical coherence tomography (SS-OCT) biometers, IOLMaster 700 (biometer A, Carl Zeiss Meditec AG) and ANTERION (biometer B, Heidelberg Engineering GmbH) and 1 optical low-coherence reflectometry (OLCR) device (biometer C, LENSTAR, LS900; Haag-Streit AG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 29 publications
6
54
1
Order By: Relevance
“…In terms of CCT measurement, excellent repeatability was con rmed by the small COR (1.94µm) and CoV (0.131%) scores and the ICC of 0.9996 from the current study. Measurements of CCT from MS-39 produced mean values (535.99 ± 34.17 µm) comparable to those previously reported using SS-OCT on healthy eyes [18][19][20][21][22][23]. Previous studies on myopic eyes showed that Pentacam HR rotating Scheimp ug camera and Sirius Scheimp ug camera-Placido topographer (CSO, Scandicci, FI, Italy) achieved inferior repeatability [24][25][26].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In terms of CCT measurement, excellent repeatability was con rmed by the small COR (1.94µm) and CoV (0.131%) scores and the ICC of 0.9996 from the current study. Measurements of CCT from MS-39 produced mean values (535.99 ± 34.17 µm) comparable to those previously reported using SS-OCT on healthy eyes [18][19][20][21][22][23]. Previous studies on myopic eyes showed that Pentacam HR rotating Scheimp ug camera and Sirius Scheimp ug camera-Placido topographer (CSO, Scandicci, FI, Italy) achieved inferior repeatability [24][25][26].…”
Section: Discussionsupporting
confidence: 74%
“…The repeatability of ACD was similar with that reported by Savini et al [16], although the ACD acquired in this study was slightly deeper, potentially due to the different population enrolled. Moreover, the new SD-OCT/Placido topographer showed higher repeatability in ACD measurements than those obtained from Scheimp ug cameras [24] and SS-OCT [20][21][22][23].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The coefficient of variance (CoV) can be used to express the precision and repeatability of a measurement, where lower CoV values indicate higher accuracy. This metric has previously been used to report the quality of a measurements obtained with different biometers, including the IOLMaster and Pentacam [ 15 , 16 , 17 , 18 ]. In 2017, Ruiz-Mesa et al compared a Scheimpflug/PCI-based system with an optical low-coherence reflectometry (OLCR) device.…”
Section: Discussionmentioning
confidence: 99%
“…The latest biometers yield even better results: in a prospective clinical trial presented in 2021, Fişuş et al included 50 routine cataract patients to compare the repeatability of two SS-OCT biometers, the IOLMaster 700 and the Anterion (Heidelberg Engineering GmbH, Heidelberg, Germany), and one OLCR device, the Lenstar LS 900 (Haag-Streit AG, Köniz, Switzerland). For AL values, the CoV ranged between 0.006 and 0.012% [ 17 ]. In another recent study by Shetty et al comparing the Lenstar LS 900, IOLMaster 700, and Anterion, the CoVs for AL ranged between 0.029 and 0.058% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%